The effects of Tai Chi on glucose and lipid metabolism in patients with diabetes mellitus: A meta-analysis - Wang Xinzheng; Jin Fanyuan; Wang Xiaodong (Elsevier, 2022)
Objective: The research aims to evaluate effects of the Tai Chi exercise therapy on glucose and lipid metabolism in patients with type 2 diabetes mellitus (T2DM). Design: Systematic review and meta-analysis of existing literature were undertaken. Methods: Seven electronic resource databases were scanned to collect eligible studies. Two reviewers selected studies, the meta-analysis was performed with RevMan 5.3 after quality evaluation. Results: Nineteen RCT trails involved in 18 reports were included in the meta-analysis, involving 1220 research objects. The results show that the Tai Chi exercise group is better than the control group in decreasing fasting blood glucose (FBG) (MD = − 0.79, 95 %CI (− 1.73, − 0.68), p < 0.0001), glycated hemoglobin (HbA1c) (MD = − 1.10, 95 % CI (− 1.78, − 0.43), p = 0.001), triglyceride (TG) (MD = − 0.23, 95 % CI (− 0.32, − 0.15), p < 0.0001) and in increasing the concentration of high-density lipoprotein cholesterol (HDL-C) (MD = 0.15, 95 % CI (0.11, 0.20), p < 0.0001) of T2DM patients. Conclusions: Tai Chi exercise therapy shows significant superiority in improving the FBG, HbA1c, TG, and HDL-C in T2DM patients. It can be used as one of the exercise prescriptions for prevention and treatment of T2DM patients.